Queer Teachers, Identity and Performativity - Harris, Anne.; Gray, Emily M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
What do we mean when we talk about'queer teachers'? The authors here grapple with what it means to be sexually or gender diverse and to work as a school teacher within four national contexts: Australia, Ireland, the UK and the USA. This new volume offers academics, educators and students a provocative exploration of this pivotal topic.
Keywords: Science; Science; Science, general